The rhoptry proteome of Eimeria tenella sporozoites - Oakes, R; Kurian, D; Bromley, E; Ward, C; Lal, K; Blake, D; Reid, A; Pain, A; Sinden, R; Wastling, J; Tomley, F (2013)
Proteins derived from the rhoptry secretory organelles are crucial for the invasion and survival of apicomplexan parasites within host cells. The rhoptries are club-shaped organelles that contain two distinct subpopulations of proteins that localise to separate compartments of the organelle. Proteins from the neck region (rhoptry neck proteins, RON) are secreted early in invasion and a subset of these is critical for the formation and function of the moving junction between parasite and host membranes. Proteins from the bulb compartment (rhoptry protein, ROP) are released later, into the nascent parasitophorous vacuole where they have a role in modifying the vacuolar environment, and into the host cell where they act as key determinants of virulence through their ability to interact with host cell signalling pathways, causing an array of downstream effects. In this paper we present the results of an extensive proteomics analysis of the rhoptry organelles from the coccidian parasite, Eimeria tenella, which is a highly pathogenic parasite of the domestic chicken causing severe caecal coccidiosis. Several different classes of rhoptry protein have been identified. First are the RON proteins that have varying degrees of similarity to proteins of Toxoplasma gondii and Neospora caninum. For some RON families, E. tenella expresses more than one gene product and many of the individual RON proteins are differentially expressed between the sporozoite and merozoite developmental stages. The E. tenella sporozoite rhoptry expresses only a limited repertoire of proteins with homology to known ROP proteins from other coccidia, including just two secreted ROP kinases, both of which appear to be equipped for catalytic activity. Finally, a large number of hitherto undescribed proteins that map to the sporozoite rhoptry are identified, many of which have orthologous proteins encoded within the genomes of T. gondii and N. caninum. © 2012 .